Melihat Teologi Kontekstual Model Transendental dalam Ritual Ma’pakande Tomate dalam Konteks Budaya Toraja - Novitasari Novitasari; Debyanti Noro’ Palullungan; Helga Helga; Liska Tiropadang; Wiranda Upa (Jurnal Magistra, 2024)
This article contains the Transcendental Model of Contextual Theology in the Ma'pakande Tomate ritual in Toraja society. Transcendental is understood as the belief that a person has, he realizes that there is a power outside himself that benefits him. The Toraja tribe has a belief called Aluk Todolo, they believe that To Membali Puang or To Dolo must be worshiped and glorified because in the future he will become one of the third persons next to Puang Matua and Deata-deata. The purpose of this writing is to see how the transcendental model of contextual theology is present in the Ma'Pakande Tomate ritual in the context of Toraja society.